Product Development System in Pattern Construction System, Standard Body Measurement and Suitable Fitting Allowance for Thai Ladies Brand in Fashion Industry - Foengfurad Mungtavesinsuk (Agriculture and Natural Resources, 2007)
Concept of the brand, theme of the design is the spirit of the collection in the fashion branding. But the Pattern Construction System, standard body measurement and suitable fitting allowance are the sustainable part for the branding in the market. The study found that most brands in Thailand did not correct and less detailed, about body measurement, standard sizing with appropriate fitting allowance for pattern construction and the pattern construction system. The objectives of this research, firstly the author used the Germany Pattern System and appropriate German standard body measurements to make pattern construction. The results showed that humans with different figures (and it does not matter in which country), the body type selected and the size range of body measurement are almost similar. Secondary, German Standard fitting allowance was applied to the Thai fashion industry. The results showed that the tight fit should be used for the first or second step (of fitting allowance) and the blouse item in second or third step of fitting allowance, etc. Additionally, the study found that through systemization, productivity increased and the cost of the product development was reduced.